2021
DOI: 10.3390/infrastructures6090126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Bonding Potentials of Trackless Tack under a Thin Overlay

Abstract: Trackless tacks are used to minimize the loss of tack materials caused by adherence to moving tires. During the last two decades, the paving industry and highway agencies have had an increasing interest in the use of trackless tacks to ensure an adequate bond between the overlay and the existing pavement. Therefore, the need for more studies on the bonding characteristics of various trackless tacks is growing. The purpose of this study is to measure the bonding potential of trackless tacks and identify several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…To provide a broader perspective, a comparison of the results obtained in this study with those reported by other authors supports the effectiveness of the newly developed trackless tack coat in improving adhesion strength, tensile bond strength, and shear behavior. These results are consistent with prior research by various authors, including Dian et al (2018) [38], Seo et al (2021) [27], and Peng et al (2023) [25]. By considering the collective evidence, it becomes evident that the trackless tack coating method offers superior performance compared to conventional tack coating methods.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To provide a broader perspective, a comparison of the results obtained in this study with those reported by other authors supports the effectiveness of the newly developed trackless tack coat in improving adhesion strength, tensile bond strength, and shear behavior. These results are consistent with prior research by various authors, including Dian et al (2018) [38], Seo et al (2021) [27], and Peng et al (2023) [25]. By considering the collective evidence, it becomes evident that the trackless tack coating method offers superior performance compared to conventional tack coating methods.…”
Section: Discussionsupporting
confidence: 90%
“…One approach is to use simultaneous installation equipment, such as the Spray Paver shown in Figure 2, which attaches a tack coat spraying device to the asphalt paver and spreads the asphalt mixture while spraying the tack coat. The simultaneous laying method prevents tack coat loss caused by transport trucks and pavers by spraying the tack coat from the lower part of the paver to the back of the paver track and in front of the screed [27,28,33]. Although this method can prevent tack coat loss, it cannot secure tack coat curing time during the construction process.…”
Section: General Conceptmentioning
confidence: 99%
See 1 more Smart Citation